LEGAL PROTECTION FOR PUBLIC ACCOUNTANTS AGAINST FAILURE TO DETECT FINANCIAL REPORTING FRAUD - Subri, Anderson; Surono, Agus; Hamid, Adnan (International Journal of Social Service and Research, 2025)
The purpose of this study is to explore the ideal concept of professional legal protection in protecting the public interest from financial reporting fraud. The research employed a normative juridical law method, focusing on doctrinal legal research, to gather comprehensive insights into the challenges and perceptions surrounding legal protections for public accountants. Thematic analysis categorized the findings to provide a coherent understanding of the gaps and challenges in the current legal system, ultimately striving to enhance the legal framework surrounding the Public Accountant profession. The evaluation of potential reforms based on principles of justice offers a pathway toward enhancing the legal system surrounding the public accounting profession.